Interactive Lesson Video Model To Develop Pronunciation Skill The Tenth Grade Students’ English Pronunciation Skill : Research And Development. - arif nurfauzan; Supriyono; Miza Rahmatika Aini (JARES (Journal of Academic Research and Sciences), 2022)
This research was aimed to develop interactive video model for teaching pronunciation to the tenth grade students. This strategy was choosen because it could interested the students to learn pronunciation. The researcher applied Research and Development (R&D) design. The subject of this research was students of senior high school. The data of the research were quantitative and qualitative data. The quantitative data were the outcome of the pre-test and post-test results with included the results of experts content material and experts content of media toward the developed interactive video model. Based on the recapitulation results of interactive video model, the presentage of component mterial was 86,06% and the results of media was 84,74%. the results recapitulation of students mean score in students learning with interactive video model in pre-test was 62,58 and post-test was 75,70. It means the interactive video model included in “very feasibility” category. So, the interactive video model can use to teach reading in the classroom.